Mating and oviposition behavior in the legume pod borer, Maruca testulalis - Jackai, L.; Ochieng, R.S.; Raulston, J.R (1990)
Experiments were conducted outdoors and in the insect rearing laboratory at the International Institute of Tropical Agriculture (IITA) in Nigeria. Four or five nights pairing duration gave the highest mating percentage and oviposition by the pod borer. Direct observations on adult mating revealed that some males mated more than once. The majority of females mated only once. A one-to-one ratio (with 10 males: 10 females) gave the best results for mating and oviposition. Mating took place between 21.00 h and 05.00 h when temperature ranged between 20–25 °C and rh over 80% with peak activity occurring between 02.00 and 03.00 h. Oviposition followed a similar trend to that observed for mating with an equal sex ratio (of 10 or more pairs per cage) giving the highest egg count. The average number of eggs laid was ca. 400 per female. These results show a much higher oviposition potential for Maruca testulalis than has been previously reported. The results are discussed with regard to the rearing of this species under laboratory conditions.